(untitled) (Global Journal of Management and Business Research, 2021)
With the steady development of information technology, new media plays a key role in enterprise marketing. It has very high coverage, can effectively spread the information of the enterprise, and help build enterprise culture. While promoting the innovation and development of enterprises, precision marketing realized at a lower cost, which helps to achieve the interaction between enterprises and consumers, plays a critical role in promoting the diversification of the consumer market and promoting the economic development of enterprises.